Pengaruh Gaya Kepemimpinan Dan Produktifitas Kerja Terhadap Kinerja Pegawai Pada Kantor Rumah Tahanan Negara Kelas IIB Sukadana Kabupaten Lampung Timur - Sobirin, Sobirin; Ratmono, Ratmono (Jurnal Manajemen DIVERSIFIKASI, 2021)
This study aims partially to determine 1) whether leadership style effects employeeperformance, 2) whether productivity effects employee performance, 3) simultaneouslywhether leadership style and work productivity affect employee performance.This type of quantitative research. With the sampling technique used, namely accidentalsampling, which means the technique of determining the sample by chance, namely theemployees of the Sukadana class IIB Prison and the sample in this study was 48employees, while the data collection techniques used were questionnaires, validity tests,normality tests, and tests. linearity, and multiple linear regression with drawing conclusionsthrough the partial t test and F simultaneous test.The conclusion of this research is that partially leadership style has no influence onemployee performance so it is necessary to re-evaluate the leadership style so that it iscarried out properly and optimally, and work productivity has shown good results inimproving employee performance, while simultaneously leadership style and workproductivity have good influence in order to improve employee performance.